1995
DOI: 10.1128/iai.63.7.2797-2800.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a protective outer membrane lipoprotein of Actinobacillus pleuropneumoniae serotype 5

Abstract: The gene encoding an outer membrane lipoprotein (omlA) of Actinobacillus pleuropneumoniae serotype 5 was cloned, and the protein was expressed in Escherichia coli. One open reading frame of 1,104 bp was detected that encoded a protein (OmlA) with a predicted molecular mass of 40 kDa. A comparison with the omlA gene and the corresponding protein of A. pleuropneumoniae serotype 1 (G.-F. Gerlach, C. Anderson, S. Klashinsky, A. Rossi-Kampos, A. A. Potter, and P. J. Wilson, Infect. Immun. 61:565-572, 1993) revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 18 publications
(15 reference statements)
1
34
0
1
Order By: Relevance
“…The antiserum also reacted very weakly with 43 kDa proteins of serotypes 5a, 5b, and 10 ( Fig. 3) although the antiserum against OmlA S has not reacted with OmlA U [9,10].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The antiserum also reacted very weakly with 43 kDa proteins of serotypes 5a, 5b, and 10 ( Fig. 3) although the antiserum against OmlA S has not reacted with OmlA U [9,10].…”
Section: Resultsmentioning
confidence: 95%
“…The ¢rst 134 amino acids of OmlA U were identical to those of OmlA S . However, the proteins have been reported to be antigeni-cally distinct, based on the fact that antiserum against OmlA S did not react with OmlA U in Western blot analyses [9,10]. These data indicate that the major epitopes a¡ecting antigenic variations are located in the amino acids downstream of the positions at 135 of OmlA S and OmlA U .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A search of GenBank sequences and subsequent sequence alignments revealed that the deduced amino acid sequence of PlpE has 18% identity and 32% similarity to an outer membrane lipoprotein (OmlA) produced by Actinobacillus pleuro- pneumoniae serotype 1 and 20% identity and 35% similarity to the OmlA protein from A. pleuropneumoniae serotype 5 (data not shown). Although both of those proteins lack the hexapeptide repeat mentioned above, they contain regularly spaced PK and PQ repeats in the same region (4,17,23).…”
mentioning
confidence: 99%
“…La inmunización de cerdos con estas proteínas confiere cierta protección frente a la infección (Chiang et al, 1991;Rossi-Campos et al, 1992;Gerlach et al, 1993;Bunka et al, 1995).…”
Section: Proteínas De Membrana Externa Tbpa Y Tbpbunclassified